Formulasi Gel NLC Ekstrak Kalus Daun Murbei Hasil Induksi dengan NAA dan BAP - Faizatun Faizatun; Erlindha Gangga; Sarah Anindita; Titiek Martati; Nur Miftahurrohmah (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
Mulberry Leaf (Morus alba L.) contains oxyresveratrol has the potential as a skin lightener. The activity of mulberry leaf callus from tissue culture is unknown as an inhibitor of the tyrosinase enzyme. The purpose of this study was to determine the activity callus extracts of mulberry leaf which obtained from tissue culture with the addition of growth regulator NAA 1.0 ppm and BAP 2.5 ppm and to formulate callus extract in Nanostructured Lipid Carrier and its characteristics. Callus was extracted by maceration-sonication. NLC is made by solvent evaporation method, NLC characterization including particle size, polydispersity index, zeta potential and particle morphology. The best NLC was made into a gel and evaluated organoleptic, viscosity, flow properties, pH, and tyrosinase enzyme inhibitory on extracts and NLC gels. The characterization of NLC includes particle size of 189.8 nm-632.8 nm; polydispersity index, 0.387-0.582. The morphology of NLC were spherical and zeta potential of -7.37 mV. NLC gel was semi-solid, greenish yellow, homogeneous, viscosity 530000 cPs, plastic thixotropic flow properties, pH 5.26, and inhibitory activity of tyrosinase enzymes (IC50) of callus extract and NLC gel has 72.51 µg/ml and 79.69 µg/ml, respectively. It can be concluded that callus extract of Mulberry leaf can be prepared into Nanostructured Lipid Carriers, NLC gels are physically and chemically stable and have the potential of lightening activity.